Increased reservoir ages and poorly ventilated deep waters inferred in the glacial Eastern Equatorial Pacific - de la Fuente, Maria (Nat Commun, 2015)
Consistent evidence for a poorly ventilated deep Pacific Ocean that could have released its radiocarbon-depleted carbon stock to the atmosphere during the last deglaciation has long been sought. Such evidence remains lacking, in part due to a paucity of surface reservoir age reconstructions required for accurate deep-ocean ventilation age estimates. Here we combine new radiocarbon data from the Eastern Equatorial Pacific (EEP) with chronostratigraphic calendar age constraints to estimate shallow sub-surface reservoir age variability, and thus provide estimates of deep-ocean ventilation ages. Both shallow- and deep-water ventilation ages drop across the last deglaciation, consistent with similar reconstructions from the South Pacific and Southern Ocean. The observed regional fingerprint linking the Southern Ocean and the EEP is consistent with a dominant southern source for EEP thermocline waters and suggests relatively invariant ocean interior transport pathways but significantly reduced air–sea gas exchange in the glacial southern high latitudes.